Primary Paratesticular Osteosarcoma: Case Report and A Review of the Literature - Anwar Al-Masri; Mubarak Al-Shraim; Ahmad Abu Al-Samen; Runjan Chetty; Andrew Evans (The Scientific World Journal)
Primary paratesticular osteosarcoma is an extremely rare malignancy and, to date, only a few cases have been reported. To our knowledge, no such case arising directly from paratesticular soft tissue has been described. We describe a 52-year-old man who presented with left scrotal swelling and an excisional biopsy that revealed a sarcomatous lesion. Left inguinal orchiectomy was performed and histologic examination of the extensively sampled lesion revealed a pure paratesticular osteosarcoma. The patient died 6 months after the diagnosis with disseminated disease.